A dairy mixture fortified with iron and zinc improves hemoglobin levels in children aged 2 to 10 years in an andean community in Peru: Randomized, double-blind controlled trial - Paz-Olivas, Youmi (2021)
Objetive: Previous research agrees that food fortification is the best long-term strategy for preventing iron deficiency. Our goal is to evaluate the effect of a dairy mixture fortified with iron and zinc on hemoglobin levels in children aged 2 to 10 years. Material and methods: A randomized, double-blind, controlled clinical trial was conducted in a community located 2,590 meters above sea level. Children with normal levels of hemoglobin or mild anemia were included. We assign participants to receive the iron-zinc-fortified dairy mixture or an unfortified dairy mixture. The supplement was administered five days a week for 24 weeks. Our main result was the corrected hemoglobin level taking into account the height above sea level and anthropometric indices were evaluated as a secondary result. The magnitude of the difference observed between the groups was estimated by the Student t-test. All analyzes were done with the intention to treat. Results: 67 children were randomly assigned, intervention: n=32 and control: n=35. The mean age was 5.8 years; 30 were women. Hemoglobin at the end of the follow-up was 13.1 g/dL (0.9) in the experimental group, while, in the control group, it was 12.1 g/dL (0.8); p <0.001. Likewise, a positive difference was evidenced in the anthropometric indicators in the experimental group. Conclusion: Dairy mixture fortified with iron and zinc increases hemoglobin levels and anthropometric indices in children from 2 to 10 years old.